Convergence of Regional Income Among Provinces in Kalimantan - Imaduddin, Fikrie Lazuardi; Kharisma, Bayu (Ekonomi dan Bisnis, 2024)
The Indonesian economy shows that Kalimantan has an important role in the national economy, contributing 8.45% in 2014, placing it as the third largest after Java and Sumatra. However, there are income disparities between provinces in Kalimantan, resulting in disparities in economic development. Therefore, the government must gradually increase investment and the industrial sector to even out income distribution. This research aims to analyze the Kalimantan provinces' sigma and beta convergence. The results indicate that the provinces' economies in Kalimantan still need to be fixed. The per capita income dispersion level from 2000-2021 has improved, or sigma convergence has occurred. Through dynamic panel data analysis, it was found that absolute and conditional beta convergence occurred at levels throughout the Kalimantan region. The conditional beta convergence rate shows that the variables representing production factors can accelerate the convergence rate. Variables influencing income growth and the convergence process are FDI, DI, Industry, and locally generated revenue.   Keywords: Economic Growth, Convergence, Investment, Industry, Fiscal.